The impact of financial liberalization on private savings: The case of Maghreb countries Arabia - Maher, Zaied (Quantitative Economics and Management Studies, 2025)
The concept of financial liberalization emerged in the early 1970s from the work of McKinnon (1973) and Shaw (1973). These authors presented financial sector liberalization as one of the ways in which financial development could positively influence economic growth. This theory was well received by international organizations (the International Monetary Fund and the World Bank). They proved that a policy of financial liberalization is essential to promote economic development. This work is based on the following assertion: financial liberalization ensures better mobilization and allocation of resources. It also ensures a better match between investment and savings. At this level, the aim of this article is to verify the effect of financial liberalization on private savings. To answer this question, we use the ordinary least squares method and the stationarity process to investigate the relationship between financial liberalization indicators and private savings in the Maghreb Arab countries over an 8-year period from 2000 to 2008. The econometric analysis showed that the economic growth achieved in Maghreb Arab countries during the study period reflected an increase in real per capita income, and also contributed to an increase in private savings.